Quenched fractions in the IllustrisTNG simulations: comparison with observations and other theoretical models - Donnari, Martina; Pillepich, Annalisa; Nelson, Dylan; Marinacci, Federico; Vogelsberger, Mark; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2021)
We make an in-depth comparison of the IllustrisTNG cosmological simulations with observed quenched fractions of central and satellite galaxies, for Mstars = 109-12 M⊙ at 0 ≤ z ≤ 3. We show how measurement choices [aperture, quenched definition, and star formation rate (SFR) indicator time-scale], as well as sample selection issues (projection effects, satellite/central misclassification, and host mass distribution sampling), impact this comparison. The quenched definition produces differences of up to 70 (30) percentage points for centrals (satellites) above ∼1010.5 M⊙. At z ≳ 2, a larger aperture within which SFR is measured suppresses the quenched fractions by up to ∼50 percentage points. Proper consideration of the stellar and host mass distributions is crucial: Naive comparisons to volume-limited samples from simulations lead to misinterpretation of the quenched fractions as a function of redshift by up to 20 percentage points. Including observational uncertainties to theoretical values of Mstars and SFR changes the quenched fraction values and their trend and/or slope with mass. Taking projected rather than three-dimensional distances for satellites decreases the quenched fractions by up to 10 per cent. TNG produces quenched fractions for both centrals and satellites broadly consistent with observations and predicts up to ∼80 (90) per cent of quenched centrals at z = 0 (z = 2), in line with recent observations, and higher than other theoretical models. The quantitative agreement of TNG and Sloan Digital Sky Survey for satellite quenched fractions in groups and clusters depends strongly on the galaxy and host mass range. Our mock comparison highlights the importance of properly accounting for observational effects and biases.
Gesehen am 07.02.2022